Role of Stakeholder Participation in Zero Waste in Kampoeng Sinaoe Sidoarjo - Ridiatno, Arta; Rahmanita, Myrza; Hermantoro, Hengky (LPPM Institut Pendidikan Nusantara Global, 2025)
Environmental pollution caused by inadequate waste management is a pressing issue in Indonesia, particularly due to improper handling of household waste, low public awareness, and insufficient local government resources. The challenge is compounded by a significant daily waste accumulation 575 tons in Sidoarjo, of which 227 tons is unmanaged. This journal is important as it explores the role of community engagement in promoting sustainable waste management through initiatives like the Zero Waste competition, which encourages local participation, especially among youth in Sidoarjo. Employing a quantitative research methodology, the study involved 79 respondents from the Kampoeng Sinaoe learning community, using non-probability convenience sampling. Data were analyzed through validity tests, multiple regression analysis, and Likert scales. The findings revealed that tourists play a crucial role in implementing zero waste practices, with high participation rates in activities such as recycling and waste reduction. In contrast, the local government's involvement was minimal. This research underscores the significance of stakeholder participation, particularly the community and tourists, in enhancing waste management efforts. It highlights the need for greater governmental support and local engagement to foster sustainable environmental practices, suggesting that improved collaboration can lead to more effective waste management systems in Indonesia.